Problem-based chemistry teaching - Rautiainen, Jukka (LUMAT-B: International Journal on Math, Science and Technology Education, 2016)
This article discusses the possibilities and challenges of carrying out chemistry teaching, with the help of problem-based learning (PBL). It is possible to bring out the utility of applying problem-based learning in laboratory work in higher education of chemistry. The developed activities in environmental chemistry support the promotion of teaching about sustainable development.